“Análisis de la gestión financiera y su incidencia en la toma de decisiones de la empresa de insumos agrícolas y veterinarios “AGROCARPIO” del cantón Quevedo provincia de Los Ríos en el periodo 2018-2019”. - Ortiz Michael, Vera Lady (2020)
The present investigation was carried out in the agricultural and veterinary supplies company "AGROCARPIO" in Quevedo Canton, Los Rios province. The main specific objectives of the research are to design a proposal that allows measuring the incidence of the financial management carried out in the decision making of the company. Based on the topic, the inductive methods were applied that were used in all the development of the theoretical framework, Deductive allowed to obtain important data to know the state in which the company is and analytical because an analysis was made to the records and accounting documents, in addition to which two approaches were applied, the quantitative approach in which questions were made clearly specific embodied in the surveys, qualitative approach allowed to describe details of situations, events, people, interactions, observed behaviors; The observation, interview, and survey techniques were also applied. The analysis of the acid test means that the company in its current ratio for the year 2019 has the capacity to respond with its suppliers with its assets by subtracting the inventory from to respond to its suppliers with its direct current assets. This means that the current asset is 0.06 ctvs in the short term. The higher this value is, the greater the capacity the company has to pay its debts.